On one boundary-value problem for a strongly degenerate second-order elliptic equation in an angular domain - Bazalii, B. V.; Degtyarev, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We prove the existence and uniqueness of a classical solution of a singular elliptic boundary-value problem in an angular domain. We construct the corresponding Green function and obtain coercive estimates for the solution in the weighted Hölder classes.